The Relationship Between Nutritional Status and Age of Menarche in Female Adolescent at SD Muhammadiyah Wirobrajan 3 Yogyakarta - Dewi, Anna Sastia; Rosida, Luluk (Menara Journal of Health Science, 2024)
Menarche is the most important moment for adolescent girls as it is the sign that the fertile cycle has begun. Menarche is defined as the onset of menstruation in a girl during puberty. Factors that influence the age of menarche including nutritional status, socioeconomics, physical abnormalities, audio-visual, social environment, and genetics. This study aims to determine the relationship between nutritional status and age of menarche in adolescent girls at SD (Primary School) Muhammadiyah Wirobrajan 3 Yogyakarta. The research design used analytic correlation with a cross-sectional approach. The population in this study was taken in all fourth and fifth-grade students totaling 42 students who had menstruated. The sample was determined using total sampling. The number of samples in the study were 42 fourth and fifth-grade female students who had menstruated. Data collection methods used in this study were questionnaires, observation sheets and stepping scales and microtoise. Data analysis used was chi square statistical test. The results showed that most adolescents at SD Muhammadiyah Wirobrajan 3 Yogyakarta had good nutritional status as many as 25 respondents (59.5%) and experienced normal menarche age as many as 27 respondents (64.3%). The results of data analysis obtain a P value = 0.001 (<0.05) and coefficient of contingency 0.499. It can be concluded that there is a relationship between nutritional status and age of menarche with a moderate relationship. Adolescent girls with good nutritional status will experience puberty normally. Thus, menstruation occurs normally and without interruption. However, those with more nutritional status will accelerate the arrival of menarche. Adolescent girls are expected to maintain normal nutritional status to achieve normal menarche age.